Prevalence of Ectoparasites Infesting Local Chickens in Selected Sub-Urban Communities around Katsina Metropolis, Nigeria - Suleiman, M.; Yusuf, S. H. (European Journal of Applied Sciences, 2022)
A study was conducted to investigate the occurrence of ectoparasites infesting local chickens in five sub-urban communities namely Babbar Ruga, Barhim, Kambarawa, Modoji and Morawa, around Katsina Metropolis, Nigeria. Physical examination to search for ectoparasites on both skin and feathers was performed and ectoparasite species were identified. The prevalence was observed to be higher in Modoji and Kambarawa than that of the other three communities. This study revealed that there was no significant difference (p > 0.05) in prevalence of ectoparasites infesting local chickens among the five communities. Out of the mean number of 300 chickens examined, 73.66 (24.55%) harboured ectoparasites. Also, 8.78% of male chickens were infested by ectoparasites which was not significantly (p > 0.05) different from that of their female counterparts (10.78%). Local chickens within the age group of 11 and above had the highest (8.33%) infestation, while those within the age group of 0-5 had the least (3.00%). Findings of this study also showed the prevalent rate of ticks and mites as 19.44 and 5.11%, respectively. Among the ectoparasite species identified, Argas persicus had the highest prevalence (19.44%) followed by Dermanyssus gallinae (3.11%) and Ornithonyssus syviarum (2.00%). There is need for more investigations on ectoparasites infesting local chickens in other parts of Katsina State, Nigeria.